Single and multiple cardiovascular biomarkers in subjects without a previous cardiovascular event. (October 2017) - Pareek, Manan; Bhatt, Deepak L; Vaduganathan, Muthiah; Biering-Sørensen, Tor; Qamar, Arman; Diederichsen, Axel CP; Møller, Jacob Eifer; Hindersson, Peter; Leósdóttir, Margrét; Magnusson, Martin; Nilsson, Peter M; Olsen, Michael H
Aims: To assess the incremental value of biomarkers, including N-terminal prohormone of brain natriuretic peptide (NT-proBNP), high-sensitivity troponin T (hs-TnT), high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), growth differentiation factor 15 (GDF-15), and procollagen type 1 N-terminal propeptide (P1NP), in predicting incident cardiovascular events and mortality among asymptomatic individuals from the general population, beyond traditional risk factors, including fasting glucose and renal function (cystatin C), medication use, and echocardiographic measures. Methods and results: Prospective population-based cohort study of 1324 subjects without a previous cardiovascular event, who underwent baseline echocardiography and biomarker assessment between 2002 and 2006. The clinical endpoint was the composite of myocardial infarction, invasively treated stable/unstable ischemic heart disease, heart failure, stroke, or all-cause mortality. Predictive capabilities were evaluated using Cox proportional-hazards regression, Harrell's concordance index (C-index), and net reclassification improvement. Median age was 66 (interquartile range: 60–70) years, and 413 (31%) were female. During median 8.6 (interquartile range: 8.1–9.2) follow-up years, 368 (28%) composite events occurred. NT-proBNP, hs-TnT, GDF-15, and IL-6 were significantly associated with outcome, independently of traditional risk factors, medications, and echocardiography ( p  < 0.05 for all). Separate addition of NT-proBNP and GDF-15 to traditional risk factors, medications, and echocardiographic measurements provided significant improvements in discriminative ability (NT-proBNP: C-index 0.714 vs . 0.703, p  = 0.03; GDF-15: C-index 0.721 vs . 0.703, p  = 0.02). Both biomarkers remained significant predictors of outcome upon inclusion in the same model ( p  < 0.05 for both). Conclusions: NT-proBNP and GDF-15 each enhance prognostication beyond traditional risk factors, glucose levels, renal function, and echocardiography in individuals without known cardiovascular disease.